2010
DOI: 10.1007/s00268-010-0811-y
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Approach for Sentinel Lymph Node Identification Using Fluorescence Imaging and Image Overlay Navigation Surgery in Patients with Breast Cancer

Abstract: This combined navigations of fluorescence and 3-D imaging revealed more easy and effective to detect SLN intraoperatively than fluorescence imaging alone.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
29
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(29 citation statements)
references
References 32 publications
0
29
0
Order By: Relevance
“…emitting diode light with a wavelength of 760 nm for excitation of ICG. The PDE light source also produces negligible heat, allowing continuous long-term image acquisition that makes it potentially useful for lymphatic mapping in SLNB for breast cancer, as supported by several studies [7,8,[13][14][15][16]. However, it proved difficult to detect the anatomical relationship between ICG-enhanced structures and nonenhanced surrounding tissues such as blood vessels on a monochromatic imaging monitor.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…emitting diode light with a wavelength of 760 nm for excitation of ICG. The PDE light source also produces negligible heat, allowing continuous long-term image acquisition that makes it potentially useful for lymphatic mapping in SLNB for breast cancer, as supported by several studies [7,8,[13][14][15][16]. However, it proved difficult to detect the anatomical relationship between ICG-enhanced structures and nonenhanced surrounding tissues such as blood vessels on a monochromatic imaging monitor.…”
Section: Discussionmentioning
confidence: 99%
“…Based on these methods, SLNB was established as a new standard surgical technique for patients with early breast cancer, and studies have since shown that the SLN status accurately reflects the axillary lymph node status, with a false-negative rate of <5% [2][3][4][5][6]. Nevertheless, these two methods for identifying SLNs have limitations and disadvantages, and a new method was recently developed involving a special camera system to allow imaging of invisible NIR fluorescence from circulating ICG [13][14][15][16][17][18][19].…”
Section: Discussionmentioning
confidence: 99%
“…In particular, ICG was approved for use in indicator-dilution studies by the FDA in 1958, and it is known to be one of the least toxic agents ever administered to humans, with the only known adverse reaction being rare anaphylaxis [13]. ICG emits an 800-to 840-nm fluorescence signal, has been applied in several malignancies, such as breast [14][15][16], colon [17,18], and vulva cancers [19], and has been reported to be more sensitive than infrared imaging in gastric cancer [20][21][22].…”
Section: Introductionmentioning
confidence: 99%
“…Since the introduction of ICG fluorescence imaging in breast surgery by Kitai et al in 2005 [5], this technique has been applied for the intraoperative identification of sentinel lymph nodes in patients with breast cancer. Preliminary data from recent studies has shown that this technique is feasible and accurate with acceptable sensitivity and specificity, comparable to conventional node detection methods [6][7][8][9]. Technically, ICGguided technique utilizes subareolar injection of ICG followed by real-time visualization of the lymphatic stream and subsequent sentinel lymph node biopsy guided by a fluorescence imaging system.…”
Section: Conflict Of Interestmentioning
confidence: 99%
“…With the aid of developing technology, further advances have been made in breast surgery, and subsequently, a novel technique using fluorescence imaging of indocyanine green (ICG) dye has been described [5]. To date, the published studies on this technique have assessed its role for the identification of sentinel lymph nodes as an alternative to radio-guided surgery [6][7][8][9]. Yet, this technique has never been utilized as an adjunct to the excision of nonpalpable breast lesions.…”
Section: Introductionmentioning
confidence: 99%